Genomic differentiation between swamp and river buffalo using a cattle high-density single nucleotide polymorphisms panel. (24th July 2017) - Pérez-Pardal, L.; Chen, S.; Costa, V.; Liu, X.; Carvalheira, J.; Beja-Pereira, A.
Abstract : Buffalo ( Bubalus bubalis ) is an important livestock species in many tropical and subtropical regions. In recent decades, the interest in buffalo's milk have expanded and intensive buffalo farms start to emerge. However, breeding programs and population genetics information for this species is scarce or inexistent. The present study aims to test the suitability of the commercial high-density single nucleotide polymorphisms (SNP) genotyping panel, the Illumina BovineHD BeadChip, to estimate population genetics parameters, pedigree control and identification of common variants in major production candidate genes. From a total of 777 962 SNPs included in the panel, 20 479 were polymorphic in water buffalo at a call rate of 86% and an average expected heterozygosity (HE ) of 0.306. From these, 357 were mapped within or around the flanking regions of several major candidate genes. A principal components analysis identified three different clusters, each representing pure swamp buffalo type, pure river buffalo type and admixed river buffalo. The hybrids between swamp and river buffalo were clearly identified as an intermediary cluster. The suitability of these SNPs data set for parentage and identity testing demonstrated that the combination of just 30 to 50 SNPs were enough to attain high probabilities of parentage exclusion (0.9999) in both types and identity (2.3×10 −5 and 2.0×10 −7 ) for river and swamp buffalo, respectively. Our analysis confirms the suitability of the BovineHD BeadChip to assess population structure, hybridization and identity of the water buffalo populations.